CSC301: Visual Programming / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2022)
This course covers an introduction to Visual Basic (VB) software package. Visual Basic is used to design windows applications. VB codes and experiment will be introduced during the design phase of windows applications. The aim of this course is to enable students to develop visual application, become familiar with visual development environment and use its facilities to build the applications